The Urgency Of Regulating Elements Of Community Participation In The Toll Road Investment Process In Indonesia - simon simon; Triono Eddy; ramlan ramlan (Faculty of Law, Universitas Pekalongan, 2025)
The development of toll road infrastructure in Indonesiais one of the national priorities to support economicgrowth and mobility. However, the success of this projectdepends not only on government and investor policies, butalso on the active participation of the community. Publicparticipation in toll road investment can increasetransparency, accountability, and project sustainability.This study aims to examine the urgency of regulatingelements of community participation in the toll roadinvestment process in Indonesia. The research methodused is normative juridical with an approach to analyzinglaws and regulations and case studies. The results of thestudy show that clearer and more comprehensive publicparticipation arrangements are needed to create aninclusive and sustainable investment environment. Thearrangement must include a public consultationmechanism, information transparency, and protection ofthe rights of affected communities. Thus, communityparticipation not only strengthens the legitimacy of theproject, but also contributes to the long-term success ofinfrastructure development in Indonesia